(untitled) (Belmont, 1996)
Authored by three of the nation's leading experts on the first-year experience, this Concise version of Your College Experience continues a 20-year tradition of straightforward, realistic, and intelligent coverage of the skills students need to succeed in college. This less expensive, more streamlined concise edition contains the chapters and topics instructors across the country identified as being most relevant to all kinds of students at all kinds of schools. Gardner, Jewler, and Barefoot address the goals of today’s seminar courses: helping students develop a clear sense of purpose in college, assisting them in making the right choice of academic major, and engaging them in learning — especially through the use of technology — in a manner that is both inviting and informative.
Keywords: College student orientation,Study skills,Định hướng cho sinh viên trường Cao đẳng,Kỹ năng học tập